Vibration investigation of passenger car rear suspension system under various road condition and driving maneuever - Mohd Farid, Zainudin (2010)
Suspension system plays an important role in the performance of a vehicle, especially vehicle handling and ride comfort. The objective of this project is to analyze the results in vibration of passenger car rear suspension system under various road conditions and driving maneuver. Experimental analysis was performed on the passenger car rear suspension system. The data collected by DEWESoft software was analyzed by using time domain analysis. In time domain analysis, the acceleration response of rear unsprung mass and suspension travel were determined by using post-processing method in Flexpro software. The maximum root mean square (r.m.s) acceleration of the unsprung mass was determined by using statistical analysis. In frequency domain analysis, the data was analyzed by using Fourier Spectral Analysis. The peak value of r.m.s amplitude of the unsprung mass acceleration was determined by using statistical analysis. The results were then evaluated by comparing them with different vehicle speed, road conditions and driving maneuver. From the results, it shows that the r.m.s acceleration of rear unsprung mass is increase as the vehicle speed increase, due to the excitation from the engine speed. The highest vehicle speed also produced response peaks at frequency range of 50 – 100Hz and 200 – 250Hz. The results also indicate that the bump road surface gives higher excitation to rear unsprung mass based on r.m.s acceleration value. Unpaved road surfaces give higher response peak in frequency range of 50 – 100Hz. Next, the results obtained shows that constant speed at constant radius cornering maneuver gives higher r.m.s acceleration value and higher response peak to rear unsprung mass.